Determination of toxic heavy metals and speciation of arsenic in seaweeds from South Korea - Khan, Naeem; Ryu, Keun Yeoung; Choi, Ji Yeon; Nho, Eun Yeong; Habte, Girum; Choi, Hoon; Kim, Mee Hye; Park, Kyung Su; Kim, Kyong Su (ELSEVIER SCI LTD, 2015)
This study aimed at determining the levels of toxic heavy metals including As, Pb, Cd, Al, Hg and As species, such as, As-III, As-V, MMA, DMA, AsB, and AsC in various edible species of seaweeds from South Korea. ICP-MS was used for determination of As, Pb and Cd, ICP-OES was used for Al, DMA was used for Hg, and LC-ICP-MS was used for As speciation. The analytical methods were validated by linearity, detection limits, precision, accuracy and recovery experiments, obtaining satisfactory results in all cases. From the results toxic heavy metals were found in the decreasing order of: Al > As > Pb-Cd > Hg. Generally concentrations of all analysed heavy metals and both organic and inorganic species of As were very low compared to PTWIs specified by JECFA and EC. Their contribution to the overall intake by the subject seafoods was found very low and thus would not pose any threat to consumers. (C) 2014 Elsevier Ltd. All rights reserved.